2021
DOI: 10.1002/ecy.3535
|View full text |Cite
|
Sign up to set email alerts
|

Using single visits into integrated occupancy models to make the most of existing monitoring programs

Abstract: A major challenge in statistical ecology consists of integrating knowledge from different data sets to produce robust ecological indicators. To estimate species distribution, occupancy models are a flexible framework that can accommodate several data sets obtained from different sampling methods. However, repeating visits at sampling sites is a prerequisite for using standard occupancy models. Occupancy models were recently developed to analyze detection/ non-detection data collected during a single visit. To … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Our findings agreed with numerous studies supporting the viability of community science in conservation (Lauret et al, 2021; McKinley et al, 2017; Walker et al, 2016) and Odonata biodiversity research (Patten et al, 2019; Rapacciuolo et al, 2017b). However, while inconclusive and of limited spatiotemporal scale, our observations of the data gap region mirror concerns about sampling biases and decision-making in community science that have also been the focus of many other studies (Archer et al, 2014; Bowler et al, 2022; Johnston et al, 2020; Millar et al, 2019; Ruete, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings agreed with numerous studies supporting the viability of community science in conservation (Lauret et al, 2021; McKinley et al, 2017; Walker et al, 2016) and Odonata biodiversity research (Patten et al, 2019; Rapacciuolo et al, 2017b). However, while inconclusive and of limited spatiotemporal scale, our observations of the data gap region mirror concerns about sampling biases and decision-making in community science that have also been the focus of many other studies (Archer et al, 2014; Bowler et al, 2022; Johnston et al, 2020; Millar et al, 2019; Ruete, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Community science initiatives have been crucial for understanding changes in biodiversity, distribution, and phenology, due to their potential to generate large volumes of data and cover broad geographical areas (Fraisl et al, 2022). The possible benefits of community science have been well-documented and could represent a viable alternative to data acquisition for projects where scarce financial or logistical resources prevent traditional, multi-visit sampling (Lauret et al, 2021). For example, in one study, youth volunteers were found to have observed proportionally higher numbers of mollusks, arachnids, and insects than the average iNaturalist user (Aristeidou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the French office for biodiversity develops and supports local monitoring programs in the French MPA network to perform photo-id data continuously, such detailed datasets represent an important asset to inform abundance of marine mammals populations (Evans & Hammond, 2004). Ecological indicators required by the Marine Strategy Framework Directive for bottlenose dolphins would benefit from integrating aerial line-transect with more data when available (Lauret et al 2021). In addition, the French Research Institute for Exploitation of the Sea (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Framework Directive for bottlenose dolphins would benefit from integrating aerial linetransect with more data when available (Lauret et al 2021). In addition, the French Research Institute for Exploitation of the Sea (i.e.…”
Section: Mediterranean Sea and Beyondmentioning
confidence: 99%
See 1 more Smart Citation